Effect of Vitamin C on Cadmium Depending Growth and Vitamin C Contents of Citrobacter Freundii - Ibrahim, Muhammad Salihu; Cakmak, Meltem; Özer, Dursun; Karatas, Fikret; Saydam, Sinan (My University, 2021)
Citrobacter freundii bacteria were grown in LB medium containing cadmium ion. In order to reduce adverse effect caused by cadmium, different concentrations of vitamin C, were added to the growth medium. While the concentration of bacteria grown was determined by spectrophotometer, the amounts of water and fat-soluble vitamins were also determined by HPLC. The cadmium concentration varied from 0 (control), to 10, 20, 40, 60, 75, 100, 125 ppm in LB growth medium. The effect of cadmium has not been observed on the growth of bacteria, up to 40 ppm, on the other hand no significant microorganism growth was observed over 150 ppm cadmium. Significant change of bacteria concentration was observed in the medium containing 75, 100 and 125 ppm Cd. Microorganism concentrations decreased 18.8, 40.5 and 45.5 percent in the growth medium containing 75, 100 and 125 ppm Cadmium respectively. With the addition of 75 ppm vitamin C to the same growth medium, microorganism concentration was decreased about 2.0, 28.0 and 31.0 percent, respectively compared to the control. In addition, fat and water-soluble vitamins in bacteria grown in cadmium-containing medium was decreased in comparison to the control (p<0.05). With the addition of 25, 50 and 75 ppm vitamin C to cadmium-containing medium, fat and water soluble vitamin concentrations were increased. As a result, it can be said that the negative effects of cadmium on bacterial growth and vitamin content can be reversed by the addition of vitamin C in to the growth medium of bacteria.
Keywords: Biyoloji